Deficiency in the cell-adhesion molecule dscaml1 impairs hypothalamic CRH neuron development and perturbs normal neuroendocrine stress axis function - Ma, Manxiu; Brunal, Alyssa A.; Clark, Kareem C.; Studtmann, Carleigh; Stebbins, Katelyn; Higashijima, Shin-ichi; Pan, Y. Albert (Frontiers in Cell and Developmental Biology, 2023)
The corticotropin-releasing hormone (CRH)-expressing neurons in the hypothalamus are critical regulators of the neuroendocrine stress response pathway, known as the hypothalamic-pituitary-adrenal (HPA) axis. As developmental vulnerabilities of CRH neurons contribute to stress-associated neurological and behavioral dysfunctions, it is critical to identify the mechanisms underlying normal and abnormal CRH neuron development. Using zebrafish, we identified Down syndrome cell adhesion molecule like-1 (dscaml1) as an integral mediator of CRH neuron development and necessary for establishing normal stress axis function. In dscaml1 mutant animals, hypothalamic CRH neurons had higher crhb (the CRH homolog in fish) expression, increased cell number, and reduced cell death compared to wild-type controls. Physiologically, dscaml1 mutant animals had higher baseline stress hormone (cortisol) levels and attenuated responses to acute stressors. Together, these findings identify dscaml1 as an essential factor for stress axis development and suggest that HPA axis dysregulation may contribute to the etiology of human DSCAML1-linked neuropsychiatric disorders.